Inside the Antisemitic Mind The Language of Jew-Hatred in Contemporary Germany - Schwarz-Friesel, Monika (The Tauber Institute Series for the Study of European Jewry, 2017)
Antisemitism is on the rise in Europe, sometimes manifest in violent acts against Jews, but more commonly noticeable in everyday discourse. This innovative empirical study examines written examples of antisemitism in contemporary Germany. Drawing on 14,000 letters and e-mails sent between 2002 and 2012 to the Central Council of Jews in Germany and the Israeli embassy in Berlin, as well communications sent between 2010 and 2011 to Israeli embassies across Europe, the authors show how language plays a crucial role in activating antisemitism across a broad spectrum of social classes, investigate the role of emotions in antisemitic argumentation patterns, and analyze "anti-Israelism" as the dominant form of contemporary hatred of Jews.